Is There a Role for Capsule Endoscopy in the Staging Work-up of Patients with Gastric Marginal Zone B-cell Lymphoma of MALT? - Al-Taie, O.; Dietrich, C. G.; Flieger, D.; Katzenberger, T.; Fischbach, W. (Zeitschrift für Gastroenterologie, 2013)
Introduction: In earlier studies, involvement of the small intestine was reported in patients with gastrointestinal lymphoma. Prospective data on the involvement of the small intestine in patients suffering from gastric extranodal MZBCL of MALT do not exist so far. In this study, we investigated the frequency of the involvement of the small intestine and the role of capsule endoscopy in patients with gastrointestinal extranodal MZBCL of MALT and of follicular lymphoma.Patients and Methods: 40 consecutive patients with gastrointestinal extranodal MZBCL of MALT (26 men, 14 women, aged 27 − 80 years), and 7 patients with known follicular lymphoma of the small intestine (5 men, 2 women, aged 34 − 63 years) underwent capsule endoscopy.Results: Involvement of the small intestine was identified by capsule endoscopy in all 7 patients with known follicular lymphoma of the small intestine. In 6 of 40 patients with gastric extranodal MZBCL of MALT abnormal findings could be observed, three of these findings indicative for lymphoma involvement of the small intestine. However, in each of these 3 cases, intestinal involvement had been already diagnosed by conventional GI endoscopy before capsule endoscopy.Conclusions: Capsule endoscopy is able to detect involvement of the small intestine in patients with gastrointestinal lymphoma. However, involvement of the small intestine seems to be rare in patients with gastric extranodal MZBCL of MALT. In summary, routine diagnostic work-up of the small intestine, e. g. by capsule endoscopy seems unnecessary because of the rare involvement of the small intestine and an excellent long-term outcome irrespective of a possible intestinal manifestation.
Keywords: MALT-Lymphoma; capsule endoscopy; small intestine